Daniel Balderston, El método Borges. Buenos Aires, Ampersand, 2021, Fuera de Serie, 347 páginas. - Martín Villagarcía (Orbis Tertius, 2022)
Daniel Balderston, El método Borges. Buenos Aires, Ampersand, 2021, Fuera de Serie, 347 páginas